MANFAAT TULISAN PENA INSPIRASI DALAM MENDIDIK KAUM MUDA DI ERA KONTEMPORER - Kasingku, Juwinner; Edwin Melky Lumingkewas; Winda Novita Warouw (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study looks at how the writings of the Spirit of Prophecy can help young people today, who face many moral and spiritual challenges. By reading and studying this article, it is hoped that young people will get better guidance for life, improve their spiritual understanding, and find positive values to deal with everyday situations. The research is qualitative and uses a literature review method. The researcher explores the benefits of the Spirit of Prophecy writings for young people in the modern world, reading different sources and articles. This study suggests ways for young people to avoid becoming too dependent on gadgets and social media, avoid an instant lifestyle, and build good relationships with others in real life. Overall, the writings of the Spirit of Prophecy play a key role in helping young people grow into strong individuals with good character, even in the face of contemporary challenges.